(untitled) (Research, Society and Development, 2022)
The study presents the leaf anatomical description of Barnebya, an endemic genus from Brazil with only two species. The objective of this work was to describe the leaf anatomy and identify diagnostic features for the taxonomy and systematics of this genus. Herborized leaves of the species B. dispar (Griseb.) WR Anderson & B. Gates and B. harleyi WR Anderson & B. Gates were rehydrated and processed according to the usual anatomical methods for light microscopy analysis. The diagnostic leaf anatomical characters are: the presence and number of accessory bundles on the petiole, conformation of the vascular bundle of the midrib, presence of trichomes, presence of ornamentation on the outer wall of epidermal cells on the abaxial face of the leaf blade and the types of single crystals. The results obtained in the present study showed and emphasize that anatomical characters related to petioles are important in the characterization of genera and characters related to leaf blades are important in the characterization of species in Malpighiaceae, corroborating previous studies and performing for the first time the anatomical description of leaves of Barnebya.